Exploring the Personality Types of Sheep Farmers and Influencing Factors in Banjarnegara Regency - Sugiarto, Mochamad; Cahyo, Danang Nur; Wakhidati, Yusmi Nur; Gandasari, Dyah (ANIMAL PRODUCTION, 2025)
This study explores the personality types of sheep farmers in Banjarnegara Regency and the influencing factors to their personality. Utilizing a quantitative approach with survey design, we collected data from 100 sheep farmers across various agroecological zones in the regency. The analysis revealed that the majority of sheep farmers were middle-aged (48.7 years on average) and extroverted (59%). Extroverted farmers tend to be younger, more open to innovation, and having higher education levels than their introverted counterparts. Logistic regression analysis identified age and education as significant factors influencing personality types (p<0.05), with older farmers were more likely introverted while extroverted farmers were associated with higher education levels. The findings suggest that personality traits drive sheep farmers in their farming practices, decision-making, and adaptability to change. This study has underscored the importance of tailored training programs and educational opportunities to enhance the productivity and welfare of sheep farmers in Banjarnegara. Future research should delve deeper into the interplay between personality types and other socio-economic factors to develop more effective empowerment strategies for livestock farmers.